mTORC1 Signaling in Individual Human Muscle Fibers Following Resistance Exercise in Combination With Intake of Essential Amino Acids - Edman, Sebastian; Söderlund, Karin; Moberg, Marcus; Apró, William; Blomstrand, Eva (Frontiers in Nutrition, 2019)
Human muscles contain a mixture of type I and type II fibers with different contractile and metabolic properties. Little is presently known about the effect of anabolic stimuli, in particular nutrition, on the molecular responses of these different fiber types. Here, we examine the effect of resistance exercise in combination with intake of essential amino acids (EAA) on mTORC1 signaling in individual type I and type II human muscle fibers. Five strength-trained men performed two sessions of heavy leg press exercise. During exercise and recovery, the subjects ingested an aqueous solution of EAA (290 mg/kg) or flavored water (placebo). Muscle biopsies were taken from the vastus lateralis before and 90 min after exercise. The biopsies were freeze-dried and single fibers dissected out and weighed (range 0.95–8.1 μg). The fibers were homogenized individually and identified as type I or II by incubation with antibodies against the different isoforms of myosin. They were also analyzed for both the levels of protein as well as phosphorylation of proteins in the mTORC1 pathway using Western blotting. The levels of the S6K1 and eEF2 proteins were ~50% higher in type II than in type I fibers (P < 0.05), but no difference was found between fiber types with respect to the level of mTOR protein. Resistance exercise led to non-significant increases (2–3-fold) in mTOR and S6K1 phosphorylation as well as a 50% decrease (P < 0.05) in eEF2 phosphorylation in both fiber types. Intake of EAA caused a 2 and 6-fold higher (P < 0.05) elevation of mTOR and S6K1 phosphorylation, respectively, in both type I and type II fibers compared to placebo, with no effect on phosphorylation of eEF2. In conclusion, protein levels of S6K1 and eEF2 were significantly higher in type II than type I fibers suggesting higher capacity of the mTOR pathway in type II fibers. Ingestion of EAA enhanced the effect of resistance exercise on phosphorylation of mTOR and S6K1 in both fiber types, but with considerable variation between single fibers of both types.